The Impact of Surgical Amputation and Valproic Acid on Pain and Functional Trajectory: Results from the Veterans Integrated Pain Evaluation Research (VIPER) Randomized, Double-Blinded Placebo-Controlled Trial. Issue 10 (2nd May 2019) - Buchheit, Thomas; Hsia, Hung-Lun John; Cooter, Mary; Shortell, Cynthia; Kent, Michael; McDuffie, Mary; Shaw, Andrew; Buckenmaier, Chester "Trip"; Van de Ven, Thomas
Abstract: Objective: To determine if the perioperative administration of valproic acid reduces the incidence of chronic pain three months after amputation or revision surgery. Design: Multicenter, randomized, double-blind, placebo-controlled trial. Setting: Academic, military, and veteran medical centers. Subjects: One hundred twenty-eight patients undergoing amputation or amputation revision surgery at Duke University Hospital, Walter Reed National Military Medical Center, or the Durham Veterans Affairs Medical Center for either medical disease or trauma. Methods: Patients were randomized to placebo or valproic acid for the duration of hospitalization and treated with multimodal analgesic care, including regional anesthetic blockade. Primary outcome was the proportion of patients with chronic pain at three months (average numeric pain score intensity of 3/10 or greater). Secondary outcomes included functional trajectories (assessed with the Brief Pain Inventory short form and the Defense and Veterans Pain Rating Scale). Results: The overall rate of chronic pain was 68.2% in the 107 patients who completed the end point assessment. There was no significant effect of perioperative valproic acid administration, with a rate of 65.45% (N = 36) in the treatment group and a rate of 71.15% (N = 37) in the placebo group. Overall, pain scores decreased from baseline to follow-up (median = –2 on the numeric pain scale). Patients additionally experienced improvements in self-perceived function. Conclusions: The rate of chronic pain after amputation surgery is not significantly improved with the perioperative administration of valproic acid. In this cohort treated with multimodal perioperative analgesia and regional anesthetic blockade, we observed improvements in both pain severity and function.